2016
DOI: 10.1111/vsu.12569
|View full text |Cite
|
Sign up to set email alerts
|

Operative Techniques and Preliminary Outcomes Following Percutaneous Endoscopic Thoracolumbar Pediculectomy in Dogs

Abstract: Pediculectomy using a percutaneous endoscopic thoracolumbar lateral approach is feasible, provides a good view of the spinal canal, and may be an alternative for treatment of disk disease in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…Surgical loupes are popular among neurosurgeons but offer only limited magnification. The use of exoscopes and endoscopes has been reported in a few veterinary reports . Video‐assisted ventral slots have been used in cadavers and in clinically affected dogs, whereas mostly cadaveric studies have been reported for the thoracolumbar and lumbosacral region, with only one report of using an endoscope in a study in live dogs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical loupes are popular among neurosurgeons but offer only limited magnification. The use of exoscopes and endoscopes has been reported in a few veterinary reports . Video‐assisted ventral slots have been used in cadavers and in clinically affected dogs, whereas mostly cadaveric studies have been reported for the thoracolumbar and lumbosacral region, with only one report of using an endoscope in a study in live dogs .…”
Section: Discussionmentioning
confidence: 99%
“…Benefits associated with MISS strategy include smaller incision, less soft‐tissue damage, less blood loss, lower complication rate, less scarring, less postoperative pain, quicker recovery, shorter hospital stay, and a quicker return to daily life activity . Although MISS is common practice in human neurosurgery, limited reports have been published on its use for the thoracolumbar spine in dogs . All these reports except one (percutaneous endoscopic pediculectomy) refer to canine cadavers.…”
Section: Introductionmentioning
confidence: 99%
“…Standard approaches to the spine, so called open techniques , involve muscle dissection from the bony elements with removal of ligaments, tendons, and bony structures, which are all important parts of the dorsal stabilizing element of the spine . Because of the frequency of spinal surgery in dogs, interest in MISS has been growing . However, most studies are limited to dog cadavers; only two reports have described MISS thoracolumbar technique in live dogs .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the frequency of spinal surgery in dogs, interest in MISS has been growing . However, most studies are limited to dog cadavers; only two reports have described MISS thoracolumbar technique in live dogs . As these studies have highlighted, there is a rationale for use of such techniques in the treatment of focal as well as multifocal intervertebral disc degenerative disorders (extrusion or protrusions).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, today's surgical trends point toward reducing the invasiveness of all surgeries. Minimally invasive surgery of the spine is now performed routinely in humans and has also been reported clinically and experimentally for the cervical and thoracolumbar regions in dogs . These studies rely either on percutaneous palpation or fluoroscopy to target the correct intervertebral disc space.…”
Section: Introductionmentioning
confidence: 99%